Disability and the labour market: a review of the empirical evidence - Melanie Jones (Journal of Economic Studies, 2008)
Purpose: This paper aims to identify and draw together key themes in the literature relating to the impact of disability on labour market outcomes. In doing so it provides an overview of issues in estimation in empirical work relating to disability. Approach: This paper reviews the existing international evidence relating to the impact of disability on labour market outcomes Findings: Regardless of country, data source or time period disability serves to reduce labour market prospects. Understanding the reasons for this requires consideration of issues such as separating discrimination from unobserved differences in productivity and preferences, the influence of heterogeneity within the disabled group and the dynamic effects of disability.  Practical implications: The paper also reviews recent evidence concerning the labour market impact of significant changes in legislation affecting the disabled, particularly the introduction of the Americans with Disabilities Act in theUS. This evidence is particularly useful to policymakers. Originality/value: A comprehensive review of the empirical evidence relating to the labour market impact of disability and the influence of recent changes in legislation. <!-- InstanceEndEditable -->